REASONS FOR THE EMERGENCE AND MANAGEMENT OF INTERPERSONAL CONFLICTS IN THE TEAM (Psychology Travelogs, 2024)
The article presents the results of a study on the causes of interpersonal conflicts within a team and various aspects of managing them. Interpersonal conflict is defined as a type of conflict, a specific interaction that occurs between two or more individuals due to differences in their views, values, interests, needs, or expectations in the process of joint activities and communication. The following manifestations of interpersonal conflicts within a team are identified: open confrontation, hidden confrontation, expression of negative emotional reactions, reduction in the quality of collaborative work, communication problems, changes in team dynamics, and a decrease in team spirit.Five groups of causes of interpersonal conflicts within a team are identified: differences in views and beliefs; personal differences and interpersonal antipathy; competition; communication barriers; and discrepancies in goals and expectations. It is found that interpersonal conflicts within a team have both negative (the emergence of psycho-emotional and material costs during conflict interactions; deterioration of the psychological climate in the organization; reduction of overall cooperation levels in the organization; hindrance of job performance due to excessive attention to the conflict situation; prolonged and complicated restoration of relationships) and positive (reduction of tension between conflict parties; identification of their capabilities; strengthening of the organization's team in overcoming external obstacles; development of innovations, encouragement of changes; creation of new rules and traditions; identification of weak points in the organization’s management) consequences for the organization.It is proven that diagnosing conflict situations, developing conflict resolution competence, and promoting anti-conflict behavior among team members ensure effective conflict management. A training program on anti-conflict behavior is proposed, which includes theoretical and practical modules. It aims to teach participants the following conflict management methods: active listening; empathy; paraphrasing; using "I-messages", the "Sandwich", "Win-Win" techniques; identifying common interests; negotiation skills; and involving third parties in conflict resolution.
Keywords: interpersonal conflicts; team; interaction; communication; emotional condition; psychological climate